Service Agents for Calendar Exchange - Kostoska, Magdalena; Velkoski, Goran; Gushev, Marjan; Ristov, Sashko; Bozinoski, Krste (My University, 2012)
With the emerging use of electronic calendars services on the Internet the users are constantly increasing the number of calendar platforms they use and the need to have them synchronized in one place is increasing. In this paper we discuss the evolution of the electronic services for calendars, and give overview of the APIs they use, along with protocols and interfaces to these services. We introduce an idea to create Calendar Service Agent as a software agent in order to exchange, modify and synchronize information about events from different calendar platforms. The solution is explained by protocols and patterns, as well as the structure and architecture, and platforms included.
Keywords: Calendar protocols, calendar services, calendar interoperability